Knowledge, competencies and attitudes regarding external post-mortem physical examination: A survey among German post-graduate trainees in general practice. (1st January 2018) - Valentini, Jan; Goetz, Katja; Yen, Kathrin; Szecsenyi, Joachim; Dettling, Andrea; Joos, Stefanie; Steinhaeuser, Jost; Flum, Elisabeth
Abstract: Background: The external post-mortem examination (EPME) is an important medical, legal and socio-economic task with far-reaching relevance; however, due to discrepancies between findings from EPMEs and actual cause of death, improvements in accuracy and quality are needed. Objectives: To investigate knowledge, competencies and attitudes regarding EPME in general practitioner (GP) post-graduate trainees. Methods: Before four post-graduate training courses on the EPME for general practitioner trainees, organized in 2014 in the German federal state of Baden-Wuerttemberg, a questionnaire on the EPME was distributed by the lecturer, completed by the GP post-graduate trainees and returned to the lecturer. The questionnaire consisted of 19 items related to three main categories: knowledge, competencies and attitudes. Results: Out of 380 GP post-graduate trainees, 128 completed and returned the questionnaire (response rate 33.7%). Less than 18% felt adequately confident in identifying a natural cause of death and less than 5% felt adequately confident in identifying an unnatural cause of death. Only 33% consistently fully uncover the corpse for the EPME. Conclusion: We found an important uncertainty in GP post-graduate trainees regarding their EPME knowledge and competencies.